ANALISIS PENGELOLAAN KEUANGAN DANA HIBAH PEMILIHAN KEPALA DAERAH TAHUN 2015 PADA KOMISI PEMILIHAN UMUM (KPU) DI KABUPATEN SIGI - Heryati, Lia; Amir, Andi Mattulada; Fattah, Vitayanti (Katalogis, 2018)
This study is aimed to: 1)determine and analyze financial management planning of election funds in 2015 at general election commission in Sigi District; 2) determine and analyze the implementation of financial management of election funds in 2015 at the general election commission in Sigi District; 3) determine and analyze the administration of financial management of election funds in 2015 at the general election commission in Sigi District; 4) determine and analyze the control of financial management of election funds in 2015 at the general election commission in Sigi District; 5) identify the cause of The General Election Commision Sigi revised its DIPA grant in 2015 election as a component of the regional budget. Type of study is descriptive qualitative with informants cinsist of: 1) The secretary of general election commission as KPA/PPK; 2) The commissioner of general election commission; 3) TAPD; 4) PP-SPM with data from observation, interviews, literature review, and documents. Technique of analysis is descriptive qualitative with interactive approach based on data reduction, data presentation, and conclusion. The result shows that the management of election funds in 2015 in the general election commission of Sigi from the perspective of planning, implementation, administration, dan control has been in line with the regulation of the Ministry of Domestic Affairs no. 13, 2006 about local finance management guidelines as well as the DIPA revisions.